Some features of the normative function of C. S. Peirce’s pragmatic maxim - Sørensen, Bent; Thellefsen, Torkild; Andersen, Christian (Signs - International Journal of Semiotics, 2008)
In order to gain the highest grade of clarity of his concepts, the polyhistor Charles S. Peirce (1839‐1914) put forth a pragmatic maxim. We get a glimpse of a maxim which is to serve the self‐controlled scientific drive for growth in the concrete reasonableness. It follows that the maxim is endowed with a special normative function; the maxim renders the meaning of clearly understood concepts as general normative rules of action, i.e. the meaning of a concept is directly assessed in the light of its contribution with which reactions it causes provides for the realization of the highest purpose of reasoning. These conditions always involve certain goals for action ‐ goals which are founded on the general way in which actions contribute to the universal process of rationalization. Mankind can and should try to contribute to the aforesaid growth, and this e.g. by using the pragmatic maxim. But this requires that mankind relentlessly tries to cultivate not only his thinking and acting habits but also his habits of feeling in accordance with the highest purpose; these efforts of cultivation fall precisely within the three normative sciences: esthetics, ethics and logic.